Egg Cortisol Exposure Enhances Fearfulness in Larvae and Juvenile Rainbow Trout. (10th November 2015) - Colson, Violaine; Valotaire, Claudiane; Geffroy, Benjamin; Kiilerich, Pia
Abstract: We investigated the effects of an early boost of cortisol exposure in rainbow trout ( Oncorhynchus mykiss ) eggs during fertilisation on subsequent behavioural responses when exposed to a sudden stimulus in larvae and juveniles. At 55 d post‐fertilisation (dpf), treatment had no effect on high accelerations occurring after a sudden event. At 146 dpf, these high accelerations were more frequent in cortisol‐treated fish than in controls. At 146 dpf also, swimming activity was increased in cortisol‐treated fish both before and after the sudden stimulus. This study underlines the important behavioural modifications in both larvae and juveniles, linked to a change in the surrounding environment of the embryo. Indeed, fish exposed to cortisol as eggs showed a higher level of fearfulness later in life. Our findings are of major interest for stress management in an aquaculture context and also allow for a better understanding of the long‐lasting effects of a permanent and/or acute stress – mediated by cortisol – that could be encountered by females, affecting population's life history trajectory.